DNA barcoding of invasive Gambusia holbrooki Girard, 1859 and Atherina boyeri Risso, 1810 inhabiting Upper Euphrates River Basin, Türkiye (vol 15, 1907, 2025) - Eroglu, Mucahit; Celik, Isilay; Dusukcan, Mustafa; Unal, Esra Mine; Coban, Mehmet Zulfu; Gunduz, Fatih; Keskin, Emre (Nature Portfolio, 2025)
[Abstract Not Available]